In-situ composite formation of vanadium carbide in CrFeCoNiCu high-entropy alloy cladded on AISI304 stainless steel - Saeed Hosseini; Mahmoud Sarkari Khorrami; Mahmoud Heydarzadeh Sohi (Journal of Materials Research and Technology)
In the present study, CrFeCoNiCu(VC)x (x = 0, 1, and 2) high-entropy alloy (HEA) composites were cladded on AISI304 stainless steel using tungsten-inert gas (TIG) cladding. For this purpose, elemental powders of Cr, Co, Fe, Ni, and Cu together with V and C were mechanically mixed, and then by adding the proper amount of polyvinyl alcohol as a binder, a uniform paste was prepared. The paste was then preplaced on the substrate and after being dried underwent TIG surface melting under the dilution-controlled condition to form HEA-clad layers with and without vanadium carbide (VC). Microstructural assessments of the layer formed without the addition of V and C revealed the formation of a single-phase solid solution HEA with FCC crystal structure in which the interdendritic segregation of the Cu-rich phase was evident. Upon adding V and C, appreciable microstructural changes occurred. In-situ VC and a solid solution with BCC crystal structure rich in Cr and V were formed along with the FCC phase. The BCC phase was in the form of lamellar eutectic with the FCC one. More interestingly, the morphology of the segregated Cu-rich phase altered from an interdendritic form to an island-like shape. Based on the variety of morphology, VC was formed either as an epitaxial growth or a primary phase from the molten material. By the increment of VC, the eutectic phase changed from lamellar to a divorced form. This was also responsible for the enhanced value of microhardness from 230 HV in the substrate to 570 HV in the CrFeCoNiCu(VC)2 high-entropy clad.